Integrated pest management: good intentions, hard realities. A review - Deguine, Jean-Philippe; Aubertot, Jean-Noël; Flor, Rica Joy; Lescourret, Françoise; Wyckhuys, Kris A.G.; Ratnadass, Alain (Springer, 2021)
Integrated Pest Management (IPM) provides an illustration of how crop protection has (or has not) evolved over the past six decades. Throughout this period, IPM has endeavored to promote sustainable forms of agriculture, pursued sharp reductions in synthetic pesticide use, and thereby resolved myriad socio-economic, environmental, and human health challenges. Global pesticide use has, however, largely continued unabated, with negative implications for farmer livelihoods, biodiversity conservation, and the human right to food. In this review, we examine how IPM has developed over time and assess whether this concept remains suited to present-day challenges. We believe that despite many good intentions, hard realities need to be faced. 1) We identify the following major weaknesses: i) a multitude of IPM definitions that generate unnecessary confusion; ii) inconsistencies between IPM concepts, practice, and policies; iii) insufficient engagement of farmers in IPM technology development and frequent lack of basic understanding of its underlying ecological concepts. 2) By diverting from the fundamental IPM principles, integration of practices has proceeded along serendipitous routes, proven ineffective, and yielded unacceptable outcomes. 3) We show that in the majority of cases, chemical control still remains the basis of plant health programs. 4) Furthermore, IPM research is often lagging, tends to be misguided, and pays insufficient attention to ecology and to the ecological functioning of agroecosystems. 5) Since the 1960s, IPM rules have been twisted, its foundational concepts have degraded and its serious (farm-level) implementation has not advanced. To remedy this, we are proposing Agroecological Crop Protection as a concept that captures how agroecology can be optimally put to the service of crop protection. Agroecological Crop Protection constitutes an interdisciplinary scientific field that comprises an orderly strategy (and clear prioritization) of practices at the field, farm, and agricultural landscape level and a dimension of social and organizational ecology.